Business Analysis of Cultivating Carp Cultivating (Cyprinus carpio) in The Nets Cage At Sipungguk Village Salo Subsdistrict Kampar District Riau Province - Hasbi Ashshiddiqi Arrosyidi; Eni Yulinda; Darwis ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in May 2017 which located in Sipungguk VillageSalo Subsdistrict Kampar District Riau Province. This study was to knew theinvestment, analyzing large input supply, knew business feasibility and knewobstacles cultivator in the development of the business of cultivating carp in the net atSipungguk Village. Methods used in this research is a method of survey with 10respondents determinatied by the purposive sampling. The result showed thatinvestment of business enlargement carp in the nets at the Sipungguk Village anaverage of IDR 9.319.300,- per cultivator. Gross income received by cultivator of thecarp an average of IDR 13.753.600,- per harvesting and net income received bycultivator of the carp an average of IDR 10.230.500,- per harvest. Financially thebusiness of cultivating carp in the nets done by cultivator of the carp at the SipunggukVillage advantageous and worthy of continued. Obstacles experienced cultivator ofthe as road access inadequate, lacking training, access to capital limited, lackingconcern the government, and riversides less smoothly.Keywords: business feasibility, carp, nets